Cities for talent Good practices for internationalisation in medium-sized European cities - Counihan, Marian; van Winden, Willem (University of Groningen Press, 2022)
An interdisciplinary volume combining academic articles with thematic case studies and commentary by policy makers and practitioners, resulting in a combination of academic research and policy recommendations for timely societal impact. Medium-sized cities across Europe are increasingly and actively attracting skilled migrants. How can these cities best manage the challenges of internationalisation? That is to say: How can they attract, facilitate and integrate skilled migrants, enabling them to contribute to the regional culture and economy, while still serving their local populations and maintaining social cohesion? In this volume, we combine academic findings with policy reflections to provide a uniquely interdisciplinary guide for academics, policy makers and professionals in local governments, universities, HRM departments, for successfully co-ordinated international talent management.